Using the Lymph Node Ratio to Evaluate the Prognosis of Stage II/III Breast Cancer Patients Who Received Neoadjuvant Chemotherapy and Mastectomy - Wu, San-Gang (Cancer Res Treat, 2015)
PURPOSE: This study was conducted to investigate the prognostic value of lymph node ratio (LNR) in stage II/III breast cancer patients who undergo mastectomy after neoadjuvant chemotherapy. MATERIALS AND METHODS: Clinical and pathological data describing stage II/III breast cancer patients were included in this retrospective study. The primary outcomes were locoregional recurrence-free survival (LRFS), distant metastasis-free survival (DMFS), disease-free survival (DFS), and overall survival (OS). RESULTS: Among 277 patients, there were 43 ypN0, 64 ypN1, 89 ypN2, and 81 ypN3 cases. Additionally, there were 43, 57, 92 and 85 cases in the LNR 0, 0.01-0.20, 0.21-0.65, and > 0.65 groups, respectively. The median follow-up was 49.5 months. Univariate analysis showed that both ypN stage and LNR were prognostic factors of LRFS, DMFS, DFS, and OS (p < 0.05). Multivariate analysis showed that LNR was an independent prognostic factor of LRFS, DMFS, DFS, and OS (p < 0.05), while ypN stage had no effect on prognosis (p > 0.05). CONCLUSION: The integrated use of LNR and ypN may be suitable for evaluation the prognosis of stage II/III breast cancer patients who undergo mastectomy after neoadjuvant chemotherapy.